Increased Anxiety and Depression Among Belgian Sexual Minority Groups During the First COVID-19 Lockdown-Results From an Online Survey - Thijs Reyniers; Veerle Buffel; Estrelle Thunnissen; Bea Vuylsteke; Magdalena Siegel; Magdalena Siegel; Christiana Nöstlinger; Edwin Wouters; Edwin Wouters (Frontiers Media S.A., 2022)
The COVID-19 pandemic most likely had a negative impact on mental health. Sexual minorities are at higher risk for adverse mental outcomes such as depression, anxiety and suicidal ideation. Such mental health disparities may have exacerbated during the COVID-19 pandemic, due to restricted real-life social contact. The study aim was to examine changes in depression, anxiety and suicidal ideation among Belgian sexual minority adults between the periods before and during the first COVID-19 lockdown. We conducted an online survey, which was disseminated by community organizations throughout Belgium in April 2020. The questionnaire included two-item Generalized-Anxiety-Disorder (GAD-2) and Patient-Health-Questionnaire (PHQ-2) measures. To assess how such symptoms and other factors (e.g., loneliness) had changed, we asked to what extent these occurred before and since the lockdown. We included 965 fully completed questionnaires in the analysis. The proportions of participants screening positive for depression and anxiety were significantly higher during the lockdown than before the lockdown, based on their reported symptoms for these periods: 29.3%% vs. 13.5% (p < 0.001), and 37.1% vs. 25.7% (p < 0.001) respectively. Lonely and young participants were more likely to acquire depression. About one in five participants reported suicidal ideation. Our findings suggest that the COVID-19 pandemic has exacerbated already existing mental health disparities between sexual minority adults and the general population. These exacerbations may be the result of increased loneliness and social isolation. The results highlight the need for stimulating and strengthening social connectedness within the LGBTQI community during and in the aftermath of the COVID-19 pandemic, and the need for maintaining mental health services for such groups during pandemic restrictions.